Pengaruh Pendekatan Tpack pada Pembelajaran Materi Struktur dan Fungsi Jaringan Tumbuhan untuk Meningkatkan Kemampuan Berfikir Kritis dan Hasil Belajar Siswa - Atip Nurwahyunani; Muthmainnah Azizy (Journal on Education, 2023)
This study aims to determine the effect of applying the TPACK approach to critical thinking skills and student learning outcomes. The design used in this research is Experimental (True Experimental Design) with Pretest-Posttest Control Design. The research subjects consisted of 72 high school students who were divided into two homogeneous classes, namely 36 students in the experimental class and 36 students in the experimental class. Students in the control class are taught conventionally and in the experimental class are taught using the TPACK approach. TPACK approach on critical thinking skills with sufficient category. Learning with the TPACK approach is more effective in improving learning outcomes than conventional learning. Cognitive learning outcomes of experimental class students with a completeness percentage of 83.47% while the control class completeness percentage of 71.66% with a difference of 0.42 which means that there is a difference that is not much different.